Integrating Critical Thinking into Extension Programming #2: Developing Critical Thinking Skills - Alexa J. Lamm (EDIS, 2015)
This 3-page fact sheet is the second in the Integrating Critical Thinking into Extension Programming, series. It examines the virtues of critical thinking to offer suggestions for integrating activities that encourage critical thinking into Extension programming. Written by Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, April 2015.